La representación de género en los spots publicitarios de perfumes de lujo en tres marcas icónicas: Dior, Paco Rabanne y Dolce Gabbana (2017 - 2022) - Macuri Mollehuara, Nadia Lucia (2025)
This document analyzes luxury perfume commercials from a gender perspective, as these are mass-consumed pieces that reproduce and disseminate feminine and masculine gender representations, as well as social norms. The objectives of this research are to analyze the binary gender representations of male and female characters, examine the role of audiovisual resources in the construction of these representations, identify common advertising resources used to communicate and persuade audiences, explore how these resources contribute to brand identities, and assess the evolution of binary gender representations in the luxury perfume commercials of Paco Rabanne, Dior, and Dolce & Gabbana aired between 2017 and 2022. The theories that support this research are gender theory, social representations, advertising, symbolic consumption, and content analysis. The methodology is qualitative, using content analysis as the main technique. The results show that female representations are related to their bodies and beauty, while male representations focus on strength and physical appearance, reflecting the presence of stereotypes. Although some representations differ from traditional ones, their presence is limited. In conclusion, despite the emergence of these new representations, stereotypes prevail, and they remain predominant.